2019
DOI: 10.1111/jfpe.13125
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkin (Cucurbita maxima) by‐products: Obtaining seed oil enriched with active compounds from the peel by ultrasonic‐assisted extraction

Abstract: Ultrasonic-assisted extraction (UAE) of the oil from the seeds/peel mixture of pumpkin using ethanol as solvent was investigated. The effects of the ultrasound, solvent volume, time, and temperature on the oil yield were evaluated. Oil extraction from the seeds by ultrasound and the mixture by Soxhlet extraction (SE) was also performed. The use of ultrasound and higher availability of ethanol (up to 6 mL g −1 sample) favored the oil removal. In the extraction kinetics, the washing step was verified in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 78 publications
1
38
0
Order By: Relevance
“…According to Gayas, Kaur, and Gul (2017) the extraction carried out at elevated temperatures causes softening of the plant tissues, promoting the removal of oil bound inside the matrix by the solvent used in the extraction process. This softening may be mainly related to an increase in the oil diffusion coefficient (Ramandi, Ghassempour, Najafi, & Ghasemi, 2017), which improves the oil diffusivity and solubility in the extraction solvent (Ramandi et al., 2017; Shirsath et al., 2017; Zhang et al., 2009), leading to a greater mass transfer (Massa et al., 2019; Ramandi et al., 2017; Zhang et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Gayas, Kaur, and Gul (2017) the extraction carried out at elevated temperatures causes softening of the plant tissues, promoting the removal of oil bound inside the matrix by the solvent used in the extraction process. This softening may be mainly related to an increase in the oil diffusion coefficient (Ramandi, Ghassempour, Najafi, & Ghasemi, 2017), which improves the oil diffusivity and solubility in the extraction solvent (Ramandi et al., 2017; Shirsath et al., 2017; Zhang et al., 2009), leading to a greater mass transfer (Massa et al., 2019; Ramandi et al., 2017; Zhang et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the fact that β-carotene is susceptible to high temperatures over long periods of time, and thus, its degradation may have occurred in the conventional extraction (Castejón, Luna, & Señoráns, 2018). Cuco et al (2019), Massa et al (2019), and Rodrigues et al (2017) also reported higher β-carotene extraction in UAE compared to conventional extraction.…”
Section: Uae and Soxhlet Extraction Comparisonmentioning
confidence: 99%
See 3 more Smart Citations